2012
DOI: 10.1073/pnas.1117060109
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the complex role of enzyme conformational dynamics in catalytic function

Abstract: Despite growing evidence suggesting the importance of enzyme conformational dynamics (ECD) in catalysis, a consensus on how precisely ECD influences the chemical step and reaction rates is yet to be reached. Here, we characterize ECD in Cyclophilin A, a well-studied peptidyl-prolyl cis-trans isomerase, using normal and accelerated, atomistic molecular dynamics simulations. Kinetics and free energy landscape of the isomerization reaction in solution and enzyme are explored in unconstrained simulations by allowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 47 publications
8
60
0
Order By: Relevance
“…17 This motion is also observed in the free enzyme, where CypA may adopt at least two distinct conformations including a 4 minor state that has a ~6% population. 18 While previous computational studies on CypA have mostly focused on and provided insight into a potential link between protein motions and overall enzyme function, [19][20][21][22][23][24] we here instead aimed to investigate to what extent simulations can describe quantitatively the free energy surface of the free protein in solution.…”
Section: Introductionmentioning
confidence: 99%
“…17 This motion is also observed in the free enzyme, where CypA may adopt at least two distinct conformations including a 4 minor state that has a ~6% population. 18 While previous computational studies on CypA have mostly focused on and provided insight into a potential link between protein motions and overall enzyme function, [19][20][21][22][23][24] we here instead aimed to investigate to what extent simulations can describe quantitatively the free energy surface of the free protein in solution.…”
Section: Introductionmentioning
confidence: 99%
“…70 The authors concluded that the activation barrier controls the catalysis, and that the dynamical effects are actually anticatalytic by a minor factor of 1/10. Note, however, that this analysis might have some problems, since the considerations of the difference between the enzyme and solution have not correctly reflected the electrostatic differences, which would require a QM/MM description.…”
Section: B Experimental Studies With Direct Theoretical Analysesmentioning
confidence: 99%
“…This indicated that overall a new set of contacts were formed and broken upon substrate association. We would like to note that PCA performed on contact space reports on features that are distinct from PCA of fluctuations in Cartesian coordinates (16,42). PCA in contact space defines conformational ensemble in terms of contacts formed and broken and thus yields more information of dynamic changes that take place upon substrate binding or catalysis.…”
Section: Mapping the Dynamical Changes In Cypa Upon Substrate Bindingmentioning
confidence: 99%
“…The suppressed catalytic activity in mutants may be a result of an increase in activation energy and not decreased dynamics (14,15). Although enzyme dynamics may not be responsible for catalytic speed up relative to the uncatalyzed reaction, CypA dynamics has been shown to be coupled to catalytic function (16). Allosteric regulation, i.e., modification of binding or catalysis at the active site due to binding of a ligand at a distal nonoverlapping site, is widespread in biochemical signaling (17,18).…”
mentioning
confidence: 99%